2018
DOI: 10.1136/bmjqs-2017-007669
|View full text |Cite
|
Sign up to set email alerts
|

Ranking hospitals: do we gain reliability by using composite rather than individual indicators?

Abstract: Combining multiple years or into multiple indicators results in more reliable ranking of hospitals, particularly compared with mortality and acute readmission in single years, thereby improving the ability to detect true hospital differences. The composite measures provide more information and more reliable rankings than combining multiple years of individual indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…The HARM score is a composite quality measurement, motivated by the fact that simple rates of risk‐adjusted morbidity or mortality may not reliably reflect hospital performance with surgery. In the literature, several composite surgical quality measurements have been described. All of these metrics are fairly new, and none seems to have been firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…The HARM score is a composite quality measurement, motivated by the fact that simple rates of risk‐adjusted morbidity or mortality may not reliably reflect hospital performance with surgery. In the literature, several composite surgical quality measurements have been described. All of these metrics are fairly new, and none seems to have been firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…We considered scenarios in which the prevalences of the three indicators across all hospitals were 0.05, 0.10, and 0.25 (Pr( Y 1 ij = 1) = 0.05, Pr( Y 2 ij = 1) = 0.10, and Pr( Y 3 ij = 1) = 0.25) as this is typical the range of prevalences occurring frequently in practice. For instance, Hofstede et al found that the median hospital-specific rate of in-hospital mortality amongst patients with colorectal carcinoma was 4.9%, while the median acute readmission rate for stroke patients was 6.1% [23]. They found that the median in-hospital mortality rate for patients with heart failure was 11.0%, while the acute readmission rate for colorectal carcinoma patients was 10.7%.…”
Section: Methodsmentioning
confidence: 99%
“…Lawson examined the rankability of SSI following colorectal surgery and found that the mean rankability was 0.65 for superficial SSI, 0.40 for deep/organ-space SSI, and 0.59 for any SSI [22]. Hofstede et al examined the rankability of in-hospital mortality for a variety of conditions or procedures [23]. They found that rankability ranged from 0.01 for patients with osteoarthritis undergoing total hip arthroplasty/total knee arthroplasty to 0.71 following hospitalization for stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In BMJ Quality and Safety , Hofstede et al 8 have addressed a common situation where providers (such as hospitals, general practices or community teams) are ranked according to their performance on a quality indicator. Rankings are used often to make direct performance comparisons between providers and used to identify positive or negative outliers.…”
mentioning
confidence: 99%
“…Hofstede et al 8 examine whether it is possible to improve the reliability of rankings based on quality measures. Two strategies are assessed: combining indicator data across several years to increase the number of events (eg, reporting readmission rates based on the number of admissions occurring over a multi-year period rather than a single year) or generating a composite measure by combining information from two or more quality indicators.…”
mentioning
confidence: 99%